Coupling of polynomial approximations with application to a boundary meshless method. (22nd July 2013) - Tampango, Yendoubouam; Potier‐Ferry, Michel; Koutsawa, Yao; Tiem, Sonnou
SUMMARY: New bridging techniques are introduced to match high degree polynomials. This permits piecewise resolutions of elliptic partial differential equations (PDEs) in the framework of a boundary meshless method introduced recently. This new meshless method relies on the computation of Taylor series approximations deduced from the PDE, the shape functions being high degree polynomials. In this way, the PDE is solved quasi‐exactly inside the subdomains so that only discretization of the boundary and the interfaces are needed, which leads to small size matricial problems. The bridging techniques are based on the introduction of Lagrange multipliers and a set of collocation points on the boundary and the interfaces. Several numerical applications establish that the method is robust and permits an exponential convergence with the degree. Copyright © 2013 John Wiley & Sons, Ltd.